2015
DOI: 10.1007/s12070-015-0942-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ewing’s Sarcoma of the Temporal Bone: A Rare Case Report and Literature Review

Abstract: Ewing's sarcoma is a malignant, round cell tumor arising from the bones and primarily affecting children and adolescent, accounting for 3 % of all childhood malignancies. Although the long bones and the trunk are typically affected, rare cases of it involving isolated bones throughout the body have been reported. Involvement of the skull bones is rare, constituting 1-6 % of the total Ewing's sarcoma cases but those affecting the cranial bones are rarer still, constituting only 1 %. We describe an 8 months old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…Based on recent studies, ES may be of neuroectodermal origin, arising from primitive neural crest cells 3. A 2015 literature review by Gupta et al , which reported all the cases of primary ES of the temporal bone from 1976 to 2014 in the English language and found only 29 cases 4. Our further extensive literature review from 2014 to July 2019 revealed 14 more cases of primary ES of the temporal bone as summarised in table 1 5–16.…”
Section: Discussionmentioning
confidence: 79%
“…Based on recent studies, ES may be of neuroectodermal origin, arising from primitive neural crest cells 3. A 2015 literature review by Gupta et al , which reported all the cases of primary ES of the temporal bone from 1976 to 2014 in the English language and found only 29 cases 4. Our further extensive literature review from 2014 to July 2019 revealed 14 more cases of primary ES of the temporal bone as summarised in table 1 5–16.…”
Section: Discussionmentioning
confidence: 79%
“…Twenty-three publications were based on a pooled total of 24 children (<18 years old) with diseases mimicking AM ( Table 2 ). 3,4,8-28 Age ranged from 10 weeks to 16 years with a male predominance (14 males, 8 females, 2 not reported). In total, 11 unique diseases were cited: acute myelogenous leukemia (AML), angiosarcoma, cranial fasciitis, Ewing sarcoma, Kawasaki disease, Langerhans cell histiocytosis (LCH), liposarcoma, melanoma, non-Hodgkin B- and T-cell lymphoma (NHL), and RMS.…”
Section: Resultsmentioning
confidence: 99%
“…28 Among children with white blood cell counts, most demonstrated leukocytosis (84.6%, 11/13). Diseases presenting with leukocytosis included AML, 10 cranial fasciitis, 12 Ewing sarcoma, 13,14 Kawasaki disease, 15 LCH, 18,19,21 NHL, 24,28 and RMS. 26 Two of 6 adults with temperature data presented with fevers (33.3%, 2/6).…”
Section: Resultsmentioning
confidence: 99%
“…20-22 Additionally, while radiotherapy is generally recommended for patients with Ewing sarcoma given that the tumor cells are extremely radiosensitive, radiotherapy is not recommended in children younger than 3 years due to the unavoidable long-term consequences of radiation. 23…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Additionally, while radiotherapy is generally recommended for patients with Ewing sarcoma given that the tumor cells are extremely radiosensitive, radiotherapy is not recommended in children younger than 3 years due to the unavoidable long-term consequences of radiation. 23 Specific management recommendations are challenging to make due to retrospective data that are subject to confounding variables such as tumor stage and age, potential for publication bias, small number of studies, lack of controlled studies, and multiple sites of disease. Therefore, we advise clinicians to use the findings of this article with their own clinical judgment to determine which treatment strategy they should pursue.…”
Section: Managementmentioning
confidence: 99%